Photoshop Elements 8 : top 100 simplified tips & tricks - Sheppard, Rob (Top 100 simplified tips & tricks., 2010)
"You already know Photoshop Elements 8 basics. Now you'd like to go beyond with shortcuts, tricks, and tips that let you work smarter and faster. And because you learn more easily when someone shows you how, this is the book for you. Inside, you'll find clear, illustrated instructions for 100 tasks that reveal cool secrets, teach timesaving tricks, and explain great tips guaranteed to make you more productive with Photoshop Elements 8"--Page 4 of cover